2018
DOI: 10.18001/trs.4.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Use among Adolescents and Young Adults: Informing Cigar Regulations

Abstract: Objectives: We used focus groups to understand cigar product features that increase the appeal of blunts (hollowed out cigars filled with marijuana) among adolescents and young adults. Methods: With a standardized focus group guide, we assessed cigar use behaviors and perceptions among lifetime cigar users (N = 47; 8 focus groups separated by sex and age group [adolescents, young adults]) in 2016. We analyzed data related to blunts. Results: Overall, 85.5% of the participants had smoked a blunt in the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Market sales data were used to identify the highest-selling US cigarillo flavors of 2016, which were categorized as (1) classic (such as original ), (2) sweet , or (3) with characterizing flavor (such as grape or wine ). For the purposes of the study, we purchased in July 2017 at least 1 cigarillo per flavor category from the 6 top selling US brands of 2016 and one brand popular with local youths …”
Section: Methodsmentioning
confidence: 99%
“…Market sales data were used to identify the highest-selling US cigarillo flavors of 2016, which were categorized as (1) classic (such as original ), (2) sweet , or (3) with characterizing flavor (such as grape or wine ). For the purposes of the study, we purchased in July 2017 at least 1 cigarillo per flavor category from the 6 top selling US brands of 2016 and one brand popular with local youths …”
Section: Methodsmentioning
confidence: 99%
“…When assessing cigarillo use, it is difficult to disentangle use of the product for smoking tobacco versus smoking blunts [31], a behavior that is particularly common among young adults [11,32,33]. This is an important distinction since research suggests that individuals may prefer different cigarillo product characteristics depending on how they intend to use the cigarillo (i.e., for tobacco or for blunt use) [11,32].…”
Section: Plos Onementioning
confidence: 99%
“…When assessing cigarillo use, it is difficult to disentangle use of the product for smoking tobacco versus smoking blunts [31], a behavior that is particularly common among young adults [11,32,33]. This is an important distinction since research suggests that individuals may prefer different cigarillo product characteristics depending on how they intend to use the cigarillo (i.e., for tobacco or for blunt use) [11,32]. For example, Giovenco et al found that young adults used different cigarillo brands for different purposes; Swisher Sweets were perceived as being used to smoke blunts, while Black & Milds were perceived as being used to smoke tobacco [11].…”
Section: Plos Onementioning
confidence: 99%
“…Three-quarters of cannabis users and two-thirds of blunt (removing tobacco from cigar wrapper and replacing with cannabis) users use cigars [30,31]. Qualitative research suggests that cigarillos are preferred for cannabis use because flavoring masks the smell [32,33] and enhances the experience of creating and smoking blunts [33]. Flavor is among the most highly valued tobacco product attributes for blunt use [34], and one study has reported that 83% of adults who have ever tried a blunt used a flavored cigar wrapper [35].…”
Section: Introductionmentioning
confidence: 99%